1982
DOI: 10.1111/j.1346-8138.1982.tb02614.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Porphyria Cutanea Tarda and Primary Liver Cancer: Report of Ten Cases

Abstract: Studies of the association between porphyria cutanea tarda (PCT) and primary liver cancer have produced conflicting reports. The incidence of this liver tumor was studied in 138 PCT patients (7.2%) and in 358 non‐porphyric cirrhotic patients (5.6%), and no statistically significant differences were found between them (p>0.5). Nevertheless the incidence of such association was significantly higher (chi square=10.91, p<0.001) in the PCT group (24.3%) than in the non‐porphyric cirrhotic group (6.7%) when only mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Of our 6 cases with PLC and PCT, 4 were alcoholics and 1 had haemochromatosis. In a series of 10 cases with PCT who developed PLC, all were alcoholics with liver cirrhosis (Solis et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Of our 6 cases with PLC and PCT, 4 were alcoholics and 1 had haemochromatosis. In a series of 10 cases with PCT who developed PLC, all were alcoholics with liver cirrhosis (Solis et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the 100 to 200-fold risk of HCC in porphyria cutanea tarda, which does not belong to the group of acute hepatic porphyrias (Berman & Braun, 1962;Kordac, 1972;Solis et al, 1982). Porphyria cutanea tarda is associated with gross liver abnormalities (Cortes et al, 1980), including cirrhosis in many patients which may be the morphological basis for HCC in this type of porphyria.…”
Section: Pathologymentioning
confidence: 99%
“…In a review [25], 12 such cases were noted; a further example has since been described by Solis ct al. [11], These cases all had photosensitive skin lesions but in several instances the pattern of porphyrin ex cretion was not consistent with true PCT.…”
Section: Discussionmentioning
confidence: 99%
“…proposed that the risk of developing hepatoma in patients with cirrhosis and PCT is greater than the risk in those with cirrhosis alone [7,8], Until recently this possible association had received scant attention else where; apart from the Czechoslovak studies there are only 12 cases of hepatoma arising in patients with PCT in the world literature [9][10][11]. The present report describes a patient with long-standing PCT who subsequently died of liver cell carcinoma.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation